Lembar Kerja Peserta Didik (LKPD) Problem Based Learning Matematika Berbasis Digital Di SMP - Hapsari, Elisabeth Reni; Herpratiwi, Herpratiwi; Sutiarso, Sugeng (Universitas PGRI Madiun, 2023)
The development of technology changes the teacher's task from a teacher in charge of delivering subject matter to a facilitator who provides convenience in learning. Today's educators are expected to have the ability to utilize modern technology as a medium to assist the teaching and learning process. In current learning, education needs to involve students actively in the learning process. Mathematics is a part of science that is certain (exact). The Problem Based Learning model is an approach that begins by giving a problem and being asked to solve the problem. One of the learning media that can be used in the learning process is LKDP (Student Worksheet). LKPD is one of the printed teaching materials that can make it easier for students to interact with the material provided. The purpose of this study is the effectiveness of digital-based problem-based learning mathematics worksheets in junior high schools. The method used in this study uses the SLR (Systematic Literature Review) method. Data collection is carried out using documentation and reviewing all articles on LKPD, Mathematics, and Problem Based Learning. Based on the results of the research that has been done, it can be concluded that LKPD based on digital media can be effectively used in the learning process, especially in problem-based learning problem-based learning.